City tourism : national capital perspectives - Maitland, Robert, 1950-; Ritchie, Brent W.; Maitland, Robert, 1950- (Wallingford, UK ; Cambridge, Mass. : CABI, 2009)
This book examines tourism in a wide range of capital cities from around the world. The book consists of 20 chapters presented in six parts. Part II focuses on issues concerning the imaging and branding of national capital cities covered by four chapters. Part III of the book focuses on visitor experiences and perceptions of national capitals and comprises four chapters. Part IV of this book focuses on specific tourism markets in capital cities and covers four distinct chapters. Part V consists of five chapters that explore the nature of tourism development in national capitals. Part VI discusses the commonalities and contrasts between the previous chapters, and presents and discusses the key aspects related to the book themes, outlined earlier. It concludes with a discussion of future research directions and priorities to expand the body of knowledge related to national capital tourism, and in doing so contributes to a better understanding of city tourism more generally.
Description based on print version record.
Includes bibliographical references and index.
All age.
Keywords: Tourism; Capitals (Cities).; Cities and towns